Development of Face Recognition Software to Differentiate Autism Spectrum Disorder from Typical Adolescents - Supra Wimbarti; Willy Kristianto Yappy (Faculty of Psychology, Universitas Gadjah Mada, 2020)
The purpose of this research was two folds: (1) to establish the face recognition software; and (2) to differentiate the ability in face recognition between Autism Spectrum Disorder (ASD) from typical adolescents. The subjects were adolescents between 10-16 years old. The experimental group consisted of 31 adolescents with ASD, the control group consisted of 32 typical adolescents. Research was done using experimental method, with face recognition software. Data collected were the number of correct faces recognized and the time needed to recognize and touch the face. The hypothesis was adolescents with ASD have worse face recognition ability compared to typical adolescents. Result showed that there were differences between ASD group compared to normal group both in the number of correct face recognitions and the time needed to choose a face with a finger touch. A one-way MANOVA revealed a significant multivariate main effect for type of groups toward the number of correct answers and time needed to answer, Wilks’ λ = 0.739, F (2,60) = 10.610, p < 0.001. The univariate main effect were also examined, whereupon significant univariate main effect for type of groups were obtained for both the amount of correct answer, F (1,61) = 15.468 p < 0.001, and the amount of time needed to answer, F (1,61) = 21.360 p < 0.001.